Three-dimensional evaluation of impacted maxillary canines and repercussions on adjacent teeth - Leitão, Rita (2024)
Maxillary canines have very important roles in aesthetics and function. They are the second most frequently impacted teeth. One of the most severe complications associated with impacted maxillary canines is root resorption of adjacent teeth. Cone-beam computed tomography (CBCT) provides three-dimensional multiplanar images and detailed information on dentofacial structures. The aim of this systematic review is to analyze impacted maxillary canines from three dimensions and analyze root resorption of the adjacent teeth caused by the impaction, based on CBCT only. The PRISMA methodology was applied, and a literature search of the last 11 years was carried out in PubMed and Scielo using the keywords “cone-beam computed tomography”, “maxilla”, “cuspid”, “root resorption”, “tooth, impacted”. This search was conducted through inclusion and exclusion criteria. The clinical relevance of this study consists of the need for adequate assessment of the location of impacted canines and degree of root resorption of adjacent teeth for surgeons and orthodontists to create an appropriate diagnosis and collaborative treatment plan. Lateral incisors were more affected by root resorption, especially when the widths of the crown, root length and volume were decreased. Female gender predominates; however, this is controversial. Some authors stated that the most common position of impacted maxillary canines is palatal. A statistically significant connection between bilaterally impacted maxillary canines and a greater number of teeth resorption was found; notwithstanding, the degree of root resorption is not consistent among authors. Their most frequent locations are palatal, mesial, and horizontal. Adjacent teeth located beyond the mesial surface, in contact with palatally impacted canines whose cusp tip is at the apical third of their roots, were likely to suffer root resorption.